2019
DOI: 10.1055/s-0039-1693144
|View full text |Cite
|
Sign up to set email alerts
|

Radioanatomical Study of the Pedicle of the Superficial Circumflex Iliac Perforator Flap

Abstract: Background The superficial circumflex iliac perforator (SCIP) flap has many ideal features, such as fast dissection, possibility to harvest thin, pliable, wide skin island, and concealed donor site scar. In spite of these features, its use was limited because of the wide anatomical variation of the pedicle, which is relatively shorter and has a smaller caliber than other more popular perforator flaps. Several names were given to the branches and perforators in the literature, thus adding confusion to the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…15,16 A recent cadaveric study came up to the same conclusion that the SCIP pedicle has a constant anatomy and it could be reliable. 17 A radioanatomical study from Gentileschi et al 18 have shown larger vessel diameters in superficial branches compared with deep branches of superficial circumflex iliac artery. 18 According to our analysis, SCIP flaps have a pedicle length and vessel diameter that could be adjusted to a wide range of recipient areas.…”
Section: Pedicle and Flap Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 A recent cadaveric study came up to the same conclusion that the SCIP pedicle has a constant anatomy and it could be reliable. 17 A radioanatomical study from Gentileschi et al 18 have shown larger vessel diameters in superficial branches compared with deep branches of superficial circumflex iliac artery. 18 According to our analysis, SCIP flaps have a pedicle length and vessel diameter that could be adjusted to a wide range of recipient areas.…”
Section: Pedicle and Flap Characteristicsmentioning
confidence: 99%
“…17 A radioanatomical study from Gentileschi et al 18 have shown larger vessel diameters in superficial branches compared with deep branches of superficial circumflex iliac artery. 18 According to our analysis, SCIP flaps have a pedicle length and vessel diameter that could be adjusted to a wide range of recipient areas. Pedicle elongation techniques could be helpful in obtaining a reasonable length of the pedicle.…”
Section: Pedicle and Flap Characteristicsmentioning
confidence: 99%
“…Reflecting the current trend toward perforator flap or supermicrosurgery, there has been an increase interest in ultrasound use in reconstructive microsurgery, especially in supermicrosurgery cases. [30][31][32][33][34] During 2019, there were at least three lymphedema symposiums, and one supermicrosurgery symposium. In 2020, the second Ultrasound Symposium for Reconstructive Microsurgery will be held in Rome.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 CTA is described to be a reliable method for perforator imaging with high spatial resolution. 32,33 Cheng et al reported in a review with three included studies that examined the accuracy of hhD for the ALTPF a sensitivity of 89.7% and a specificity of only 18.2%. 34 The authors stated that this modality is a technically feasible and affordable method but should be combined with another method for reliable perforator localization.…”
Section: Discussionmentioning
confidence: 99%